EFEK SAMPING OBAT YANG TIDAK BERHUBUNGAN DENGAN KEPATUHAN PENGOBATAN PASIEN KUSTA DI SUBANG - Tinalda Nur Amelia Wijaya; Meiyanti Meiyanti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Indonesia is currently contributing to the third highest incidence of leprosy in the world. Leprosy sufferers who do not undergo regular treatment have risk in transmitting the disease to others. Moreover, it may also cause disability problems and social impacts. Objective: This study aims to analyse relationships between drug side effects, subject characteristics and adherence to treatment of leprosy patients.Method: This was an observational analytic study with a cross-sectional research design with a sample of 115 leprosy patients. This study was conducted at four Puskesmas (Community Health Centre) of Sukasari sub-district, Subang from October to December 2021. Its data was collected by using a questionnaire consisting of patient characteristics; the MMAS-8 questionnaire was used to assess levels of the adherence and the side effects. Then the data were analysed by Chi-Square and Fisher's Exact test, with a significance level of 0.05.Results: The results of this study revealed that 60 (52.2%) of the subjects were categorized in the medication adherence with a score of 0 and 22 (19.1%) of them were relatively high adherence with a score of 1-2. Most of the 93.9% of subjects experienced drug side effects while undergoing the leprosy treatment. There was no significant relationship between drug side effects (p=0.442), genders (p=0.848), ages (p=0.275), education levels (p=0.134), types of occupations (p=0.847) and adherence to treatment of leprosy patients. Conclusion: Several factors such as drug side effects, ages, genders, education levels and occupations were not significantly related to medication adherence in the leprosy patients.